Who Pays for the Tariffs and Why? A Tale of Two Countries - Chaonan Feng; Liyan Han; Lei Li (Center for Economic Studies and ifo Institute (CESifo), 2023)
During the U.S.-China trade war, the U.S. punitive tariffs were almost entirely borne by U.S. importers. In contrast, only 68% of China's retaliatory tariffs were paid by Chinese importers. The puzzling difference between the U.S. and China is mainly driven by their different import structures and product heterogeneity in tariff pass-through. China mainly imported products with lower tariff pass-through from the U.S., such as agricultural products and aircraft, while the U.S. primarily imported products with higher tariff pass-through from China, such as electronics. Furthermore, we decompose the product-level tariff pass-through and show that a higher ratio of import demand elasticity over export supply elasticity leads to lower tariff pass-through under perfect competition.
Keywords: F13; F14; F61; 330; trade war; tariff pass-through; import structure; product heterogeneity; demand elasticity; supply elasticity